2003
DOI: 10.1590/s1519-69842003000100013
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and morphology of nucleus of the Sertoli and interstitial cells of the tambaqui Colossoma macropomum (Cuvier, 1881) (Pisces: Characidae) during the reproductive cycle

Abstract: This study allowed the characterization of the tambaqui Colossoma macropomum testes structural organization, emphasizing Sertoli and interstitial cells and analyzing morphometrically the Sertoli cell nucleus diameter and the interstitial tissue area during the reproductive cycle. Fragments of tambaqui testes were collected in the following reproductive cycle stages: immature, resting, maturation I and II, mature, and regression, and were histologically processed. The Sertoli cells were found at the periphery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
4
2
0
Order By: Relevance
“…The germinal cysts were surrounded with the cytoplasmic processes of the Sertoli cells that shared with very thin collagen fibers in formation of the wall of cysts. This resembled the results of Arenas et al, (1995) in Gambusia affinis and Nakaghi et al (2003) in Colossoma macropomum. Sertoli cells were also found surrounding the spermatogonia and this was supported by the results of Abd El-Aziz (1992) in Oreochromis niloticus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The germinal cysts were surrounded with the cytoplasmic processes of the Sertoli cells that shared with very thin collagen fibers in formation of the wall of cysts. This resembled the results of Arenas et al, (1995) in Gambusia affinis and Nakaghi et al (2003) in Colossoma macropomum. Sertoli cells were also found surrounding the spermatogonia and this was supported by the results of Abd El-Aziz (1992) in Oreochromis niloticus.…”
Section: Discussionsupporting
confidence: 91%
“…Our result revealed that the Leydig (interstitial) cells were present in the intertubular spaces with numerous blood capillaries. This result was similar to those of Van Vuren and Soly (1990) in Tilapia rendalli; Mousa (1998) in Oreochromis niloticus; Nakaghi et al, (2003) in Colossoma macropomum and Smita et al, (2005) in Ichthyophis tricolor. Leydig cells were poly gonal in shape, with ill-definite cell boundaries and had centrally located spherical nuclei.…”
Section: Discussionsupporting
confidence: 84%
“…Cx30 expression appeared to increase between stages 1 and 2 of spermatogenesis, which is consistent with the notion that gap junctional communication is involved in the control of androgen secretion [18,37,38]. This observation is consistent with RT-PCR data, which suggest an increase in cx30 mRNA levels between stages 1 and 2.…”
Section: Discussionsupporting
confidence: 90%
“…This result of the current study which revealed that, the interstitial cells of Leydig which were present in the intertubular spaces with numerous blood capillaries in both species is similar to the reports of Wepener et al (2001) in Tilapia randalii (Arnold et al, 2000) in Oreochromis niloticus (Nakaghi et al, 2003) in Colossoma macropomum and (Smita et al, 2005) in Ichthyophis tricolor. The results of the present study on Leydig cells being polygonal in shape with ill-definite cell boundaries and centrally located spherical nuclei are in line with the result of Zakariah et al (2016a, b) and El-Sakhawy et al (2011) in Clarias gariepinus (Ahmed et al, 2013) in Clarias microcephalus, in Oreochromis niloticus.…”
Section: Histomorphologysupporting
confidence: 92%